(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, who has guided us to this, and we would not have been guided had it not been for God’s guidance, and prayers and peace be uponHis Messenger is the Prophet of mercy and before the imams, and the lamp of the nation and upon his family and his noble and noble companions, and many greetings.I had a strong desire and determination to write this research, to find out its secrets and to knowThe reason for choosing it is because it is linked to the Holy Qur’an first, because it is the science thatHe will study and forget, as the Prophet, may God bless him and grant him peace, said.The research included two chapters, in the first chapter dealing with inheritance, and it included two topics.The first topic is a prelude to inheritance. This topic included two requirements. The first one dealt with inheritance.In Islam and the second requirement is the definition of inheritance linguistically and idiomatically. As for the second topic, it was divided into four